Kink band predictions in fiber composites using periodic boundary conditions. (1st January 2019) - Jensen, A.B.; Thesbjerg, J.; Wind, J.L.; Jensen, H.M.
Abstract: A finite element based scheme for modelling kink band formation in fiber composites was developed. The model is computationally efficient by requiring only a few number of fiber/matrix layers representing the microstructure of the composite material. Yet, in comparison to finite element models including many fiber/matrix layers, the model is accurate by specifying periodic boundary conditions along the sides of the representative volume elements. These periodic boundary conditions allow for a rotation of the kink band after its initiation as observed in full-scale finite element calculations and experiments. Three different computational schemes for determining the kink band rotation have been suggested and compared.